Aneurysm of the inferior vena cava with thrombosis. Issue 2 (13th January 2018) - Inoue, Masashi; Sudo, Takeshi; Yamaguchi, Megumi; Seo, Shingo; Miyamoto, Tatsuya; Misumi, Toshihiro; Shimizu, Wataru; Irei, Toshimitsu; Suzuki, Takahisa; Onoe, Takashi; Shimizu, Yosuke; Hinoi, Takao; et al.
Key Clinical Message: Inferior vena cava (IVC) aneurysms are extremely rare. Patients can be asymptomatic, have thrombosis, rupture, or pulmonary embolism. Thrombosis of the IVC aneurysm may mimic a retroperitoneal tumor. Surgical treatment of abdominal venous aneurysms with thrombosis is warranted and is necessary for the management of intraoperative bleeding and thrombosis. Abstract : Inferior vena cava (IVC) aneurysms are extremely rare. Patients can be asymptomatic, have thrombosis, rupture, or pulmonary embolism. Thrombosis of the IVC aneurysm may mimic a retroperitoneal tumor. Surgical treatment of abdominal venous aneurysms with thrombosis is warranted and is necessary for the management of intraoperative bleeding and thrombosis.